A method for preparing TBC solar cells by single deposition of silicon layer without mask

Through the maskless single-shot deposition process and differentiated laser processing, the thermal stress distribution problem caused by multiple deposition of intrinsic polysilicon layers in TBC solar cells is solved, and process simplification and performance improvement is achieved, and convex shape is used. The isolation zone structure reduces the risk of short circuit and the impact of parasitic absorption.

CN118825141BActive Publication Date: 2024-12-27HENGDIAN GRP DMEGC MAGNETICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411298025.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27
Estimated Expiration
2044-09-18

AI Technical Summary

Technical Problem

In the existing TBC solar cell preparation process, multiple deposits of intrinsic polysilicon layers result in uneven thermal stress distribution, affecting product performance and yield, and the isolation zone structure design is difficult to balance the risk of short circuit and battery efficiency.

Method used

The maskless single-shot deposition silicon layer process is adopted, and a single-shot deposition of intrinsic polysilicon layer is achieved through optimizing process steps and differentiated laser processing, and a convex isolation zone structure is designed to reduce the risk of short circuit and the impact of parasitic absorption.

Benefits of technology

The preparation steps are simplified, product performance and yield rate are improved, production costs are reduced, and short-circuit probability and parasitic absorption effects are reduced through the convex isolation zone structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118825141B_ABST
    Figure CN118825141B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of solar cells, and discloses a method for preparing a TBC solar cell by depositing a silicon layer in a single pass without a mask. First, the present invention realizes the preparation of a TBC solar cell by depositing an intrinsic polycrystalline silicon layer in a single pass without constructing a mask layer by optimizing the process steps, which can further simplify the preparation steps, effectively improve the performance and yield rate of the product, and significantly reduce the production cost at the same time. Secondly, the present invention can produce a TBC solar cell with a convex isolation region structure through an ingenious differentiated laser processing process, which can not only reduce the probability of short circuits between the p-region and the n-region, but also reduce the thickness of part of the boron diffusion layer or the phosphorus diffusion layer to reduce the influence of parasitic absorption.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solar cells, and in particular to a method for preparing a TBC solar cell by depositing a silicon layer in a single step without a mask. Background Art

[0002] The current preparation of TBC solar cells usually requires first depositing a layer of intrinsic polysilicon on the back of the silicon wafer, then converting it into a boron diffusion layer through a boron diffusion process, and then depositing another layer of intrinsic polysilicon, and then converting it into a phosphorus diffusion layer through a phosphorus diffusion process. The disadvantage of the above method is that during the two depositions of the intrinsic polysilicon layer, uneven thermal stress distribution is prone to occur, resulting in warping and fragmentation of the silicon wafer, which will significantly affect the performance and yield of the product. In addition, the two depositions of the intrinsic polysilicon layer will also greatly increase the amount of special gases used, thereby increasing costs.

[0003] To this end, the applicant has previously developed a preparation process that only requires the deposition of a single layer of intrinsic polysilicon. Specifically, after depositing the intrinsic polysilicon layer, a mask layer is constructed on its surface. Boron diffusion and phosphorus diffusion are performed successively by utilizing the blocking effect of the mask layer, and finally a boron diffusion layer and a phosphorus diffusion layer with interdigitated distribution can be obtained. However, the above method newly adds the step of preparing the mask layer, and there is still room for further simplification in the preparation process.

[0004] In addition, in order to fully improve the conversion efficiency per unit area of ​​the battery, the distance between the boron diffusion area and the phosphorus diffusion area (i.e., the insulating isolation area) is usually set to a very small width, which will increase the risk of battery short circuit. At present, the isolation area structure is usually designed as a long strip. If the isolation area of ​​this structure is wide, although it can reduce the risk of short circuit between the p-region and the n-region, it will cause the silicon substrate carrier transmission cross section to the bottom poly-Si layer to decrease, resulting in FF The value is too low; if the width of the isolation region is small, the risk of conduction between the p-region and the n-region will increase, and the poly-Si region will be too large, and the parasitic absorption will be more serious, resulting in I sc The value is low.

[0005] In summary, how to further simplify the preparation process of TBC solar cells and optimize the isolation region structure to reduce the risk of battery leakage and improve the battery FF and I sc , is a problem that needs to be solved urgently. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a method for preparing TBC solar cells by single deposition of silicon layer without mask. First, the present invention realizes the preparation of TBC solar cells by single deposition of intrinsic polycrystalline silicon layer without constructing a mask layer by optimizing the process steps, which can further simplify the preparation steps, effectively improve the performance and yield of the product, and significantly reduce the production cost at the same time. Secondly, the present invention can produce a TBC solar cell with a convex isolation region structure through a clever differentiated laser processing process, which can not only reduce the probability of short circuit between the p-region and the n-region, but also reduce the thickness of part of the boron diffusion layer or the phosphorus diffusion layer to reduce the influence of parasitic absorption.

[0007] The specific technical solution of the present invention is: a method for preparing a TBC solar cell by single deposition of a silicon layer without a mask, which specifically comprises the following steps:

[0008] S1, double-sided polishing of silicon wafer.

[0009] S2. A tunnel oxide layer and an intrinsic polysilicon layer are formed on the back side.

[0010] S3, boron diffusion, so that the intrinsic polysilicon layer is converted into a boron atomic concentration of 1E+19~1E+20 cm -3 Boron diffusion layer and BSG layer.

[0011] After boron diffusion, the intrinsic polysilicon layer on the back side of the silicon wafer can be converted into a boron diffusion layer and a BSG layer, wherein the BSG layer is located on the surface of the boron diffusion layer.

[0012] S4, laser grooving to remove the BSG layer in the designed area of ​​the phosphorus diffusion layer.

[0013] Similar to conventional TBC solar cells, the back of the silicon wafer is expected to be designed with a p-region (boron diffusion region) and an n-region (phosphorus diffusion region) distributed in a forked shape. In this step, laser grooving is used to remove the BSG layer on the surface of the pre-designed phosphorus diffusion layer area, and subsequent alkaline cleaning is used to fully expose the boron diffusion layer in this area, thereby paving the way for subsequent phosphorus diffusion.

[0014] S5. Alkaline cleaning fully exposes the boron diffusion layer in the slotted area. The non-slotted area is protected by the BSG layer and can be prevented from being corroded by alkali.

[0015] S6, phosphorus diffusion, so that the exposed boron diffusion layer is converted to a phosphorus atomic concentration of >1E+20 cm -3 Phosphorus diffusion layer and PSG layer.

[0016] Since the boron doping concentration in the boron diffusion layer is relatively low, the present invention diffuses phosphorus atoms into the boron diffusion layer through a suitable phosphorus diffusion process. When the phosphorus atom concentration is higher than the boron atom concentration, the boron diffusion layer can be inverted into a phosphorus diffusion layer, and a PSG layer is formed on the surface. Due to the presence of the surface BSG layer in the non-laser grooved area, phosphorus atoms can be effectively blocked from entering during the phosphorus diffusion process, so it can still remain as a boron diffusion layer.

[0017] S7, green laser grooving is used to remove the BSG layer and PSG layer at the junction of the boron diffusion layer (p region) and the phosphorus diffusion layer (n region), and loosen the bottom deposition layers (tunneling oxide layer, boron diffusion layer, phosphorus diffusion layer).

[0018] The green laser grooved area is the pre-designed isolation area (i.e., the insulating Gap area). After removing the BSG layer and PSG layer in this area, the isolation area can be formed after subsequent wet cleaning.

[0019] S8. Use ultraviolet laser grooving to remove the remaining BSG layer on both sides and loosen the surface of the boron diffusion layer at the bottom.

[0020] S9, removing the remaining PSG layer on both sides by ultraviolet laser grooving, and loosening the surface of the phosphorus diffusion layer at the bottom.

[0021] The purpose of S8-S9 UV laser grooving is to remove the two side parts of each remaining BSG layer and the remaining PSG layer, and loosen the surface layer of the boron diffusion layer and the surface layer of the phosphorus diffusion layer at the bottom of the groove area, paving the way for the formation of a convex isolation area structure after subsequent wet cleaning.

[0022] It should be noted that S7 of the present invention uses a green laser, while S9 and S10 use an ultraviolet laser. The present invention cleverly utilizes the fact that the penetration depth of ultraviolet laser is shallower than that of green laser, and on the basis of ensuring the removal of BSG layer and PSG layer, the sedimentary layers at different depths at the bottom can be loosened. During the green laser grooving process, the sedimentary layers (tunneling oxide layer, boron diffusion layer, phosphorus diffusion layer) at the bottom of the grooving area can be loosened, so they can be completely removed during the subsequent wet cleaning process; while the depth of ultraviolet laser grooving is shallow, so only the surface layers of the boron diffusion layer and phosphorus diffusion layer at the bottom of the grooving area can be loosened, so that in the subsequent wet cleaning process, only the surface layers of the boron diffusion layer and phosphorus diffusion layer in the area are accurately controlled to be corroded and removed, thereby forming a convex isolation area structure.

[0023] S10, removing the coating on the front and side surfaces of the silicon wafer.

[0024] S11, the silicon wafer is wet cleaned and texturized under alkaline conditions. In the area covered by the BSG layer and the PSG layer, the bottom boron diffusion layer and the phosphorus diffusion layer are protected from alkali corrosion. For other areas, due to the different depths of laser loosening in S7 and S8 / S9, the alkali corrosion rate in different areas will be different. The wet etching rate is: V (绿色激光开槽区域) >V (紫外激光开槽区域) Finally, by controlling the cleaning time, the deposition layer of the green laser grooved area on the back of the silicon wafer is removed, and the back of the silicon wafer is exposed. The surface of the boron diffusion layer and the surface of the phosphorus diffusion layer in the ultraviolet laser grooved area are removed to form a convex isolation area structure. At the same time, the surface of the isolation area on the front and back of the silicon wafer is textured to form a pyramid texture surface; finally, the PSG layer and BSG layer remaining on the back of the silicon wafer are removed by pickling.

[0025] S12, Double-sided coating: After double-sided coating, a passivation anti-reflection layer is generated on the front and back sides of the silicon wafer.

[0026] S13, screen printing, sintering, and light injection to obtain a TBC solar cell.

[0027] In summary, firstly, the present invention realizes the preparation of TBC solar cells by single deposition of an intrinsic polycrystalline silicon layer without constructing a mask layer by optimizing the process steps, thereby avoiding problems such as uneven distribution of thermal stress caused by multiple depositions of the intrinsic polycrystalline silicon layer, which leads to reduced product performance and yield rate; at the same time, it also eliminates the step of forming a mask layer, and the process steps are simplified.

[0028] Secondly, the present invention uses an ingenious preparation method to produce a TBC solar cell with a convex isolation region structure. On the one hand, although the isolation size between the bottom p-region (boron diffusion region) and the n-region (phosphorus diffusion region) does not change significantly, the isolation size between the top p-region and the n-region becomes larger, which can reduce the probability of short circuit and is beneficial to improving the yield of the battery; on the other hand, the convex isolation region structure reduces the thickness of part of the boron diffusion layer or the phosphorus diffusion layer, which can reduce the impact of parasitic absorption.

[0029] Preferably, in S3, the boron diffusion conditions are: boron diffusion temperature 800-950°C, diffusion time 5-50 min, BCl3 flow rate 50-500 sccm, O2 flow rate 500-2000 sccm; oxidation advancement temperature 900-1050°C, O2 flow rate 5000-30000 sccm; advancement time 30-80 min.

[0030] Preferably, in S3, the thickness of the BSG formed after the boron diffusion is 30-70 nm.

[0031] Preferably, in S6, the phosphorus diffusion conditions are: phosphorus diffusion temperature 750-850°C, diffusion time 10-50 min, POCl3 is carried by nitrogen with a flow rate of 1000-5000 sccm, and O2 flow rate 2000-8000 sccm; oxidation advancement temperature 850-950°C, O2 flow rate 3000-10000 sccm, and advancement time 30-90 min.

[0032] Preferably, in S6, the thickness of PSG formed after phosphorus diffusion is 30-70 nm.

[0033] As a preference:

[0034] In S7, the conditions for the green laser grooving are: laser wavelength of 477-592 nm, frequency of 500-700 KHz, marking speed of 40000-50000 mm / s, power of 40-100 W, and processing time of 1-5 s.

[0035] In S8, the conditions of the ultraviolet laser grooving are: laser wavelength of 200-400 nm, frequency of 500-700 KHz, marking speed of 40000-50000 mm / s, power of 10-40 W, and processing time of 1-3 s.

[0036] In S9, the conditions for the ultraviolet laser grooving are: laser wavelength of 200-400 nm, frequency of 500-700 KHz, marking speed of 40000-50000 mm / s, power of 8-30 W, and processing time of 1-3 s.

[0037] In addition to cleverly utilizing the difference in penetration depth of laser wavelength to assist in constructing the convex isolation region structure in S7 and S8 / S9, the present invention also controls the power of the two laser treatments. The present invention further controls the laser power of S7 to be higher and the time to be longer, while the power of the laser treatment of S8 / S9 is relatively low and the time is shorter, so that the processing depth can be further differentiated.

[0038] Furthermore, since the height of the PSG formed during the diffusion of S6 phosphorus is lower than that of the BSG layer (in a "concave" shape), in order to subsequently construct a convex isolation region structure, it is necessary to control the UV laser processing depths of the p-region and the n-region to be different (S8 is deeper). Therefore, the present invention needs to adopt a two-step process to groove the BSG layer and the PSG layer respectively, and control the power of S8 to be slightly higher.

[0039] Preferably, in S11, the width of the surface layer of the boron diffusion layer and the surface layer of the phosphorus diffusion layer removed on one side is 25-40% of the entire layer, and the height is 30-80% of the entire layer.

[0040] Preferably, in S2, the deposition conditions of the tunnel oxide layer are: O2 flow rate 10000-80000 sccm, reaction temperature 400-800°C, time 200-1000 s, and tunnel oxide layer thickness 2-10 nm.

[0041] Preferably, in S2, the deposition conditions of the intrinsic polysilicon layer are: SiH4 flow rate 300~2000 sccm, reaction temperature 500~700°C, time 2~4 h, working gas pressure 100~500 mTorr, and intrinsic polysilicon layer thickness 100~300 nm.

[0042] Compared with the prior art, the beneficial effects of the present invention are:

[0043] (1) The present invention achieves the preparation of TBC solar cells by single deposition of an intrinsic polycrystalline silicon layer without constructing a mask layer by optimizing the process steps, which can further simplify the preparation steps, effectively improve the performance and yield of the product, and significantly reduce the production cost.

[0044] (2) The present invention can produce a TBC solar cell with a convex isolation region structure through an ingenious differentiated laser processing process, which can not only reduce the probability of short circuit between the p-region (boron diffusion region) and the n-region (phosphorus diffusion region), but also reduce the thickness of part of the boron diffusion layer or the phosphorus diffusion layer to reduce the parasitic absorption effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 Schematic diagram of the structure of the silicon wafer after double-sided polishing.

[0046] Figure 2 Schematic diagram of the structure after boron diffusion of silicon wafer.

[0047] Figure 3 Schematic diagram of the structure after the first laser grooving of the BSG layer on the back of the silicon wafer + alkaline cleaning.

[0048] Figure 4 Schematic diagram of the structure of the silicon wafer after phosphorus diffusion.

[0049] Figure 5 This is a schematic diagram of the structure of the silicon wafer after cleaning and texturing.

[0050] Figure 6 Schematic diagram of the structure of TBC solar cell.

[0051] The reference numerals in the drawings are: N-type single crystal silicon wafer 1; tunneling oxide layer 2; boron diffusion layer 3; BSG layer 4; phosphorus diffusion layer 5; PSG layer 6; pyramid velvet surface 7; passivation anti-reflection layer 8; and electrode layer 9. DETAILED DESCRIPTION

[0052] The present invention will be further described below in conjunction with the embodiments.

[0053] A method for preparing a TBC solar cell by single deposition of a silicon layer without a mask specifically comprises the following steps:

[0054] S1, double-sided polishing of silicon wafer.

[0055] In some specific implementation cases, an N-type single crystal silicon wafer 1 after diamond wire cutting is selected, with a thickness of ~150 μm and a size of 182.2 mm×186.7 mm. The silicon wafer is placed in an alkaline polishing tank, the temperature is maintained at 75~85°C, and the time is 6~8 min for double-sided polishing, the polishing thickness is 3~7 μm, and the thinning amount is 0.35~0.45 g. Figure 1 shown.

[0056] S2. Form a tunnel oxide layer 2 (using LPCVD method) and an intrinsic polysilicon layer 3 (using LPCVD method) on the back side.

[0057] In some specific implementation cases, the deposition conditions of the tunnel oxide layer are: O2 flow rate 10000~80000sccm, reaction temperature 400~800°C, time 200~1000 s, and tunnel oxide layer thickness 2~10 nm.

[0058] In some specific implementation cases, the deposition conditions of the intrinsic polysilicon layer are: SiH4 flow rate 300~2000sccm, reaction temperature 500~700℃, time 2~4h, working gas pressure 100~500mTorr, intrinsic polysilicon layer thickness 100~300nm.

[0059] S3, boron diffusion, so that the intrinsic polysilicon layer is converted into a boron atomic concentration of 1E+19~1E+20 cm -3 After boron diffusion, the intrinsic polysilicon layer 2 on the back of the silicon wafer can be converted into a boron diffusion layer 3 and a BSG layer 4, wherein the BSG layer 4 is located on the surface of the boron diffusion layer 3, such as Figure 2 shown.

[0060] In some specific implementation cases, the boron diffusion conditions are: temperature 800-950°C, diffusion time 5-50 min, BCl3 flow rate 50-500 sccm, O2 flow rate 500-2000 sccm; oxidation advancement temperature 900-1050°C, O2 flow rate 5000-30000 sccm, advancement time 30-80 min. The thickness of the BSG layer is 30-70 nm.

[0061] S4, laser grooving to remove the BSG layer in the designed area of ​​the phosphorus diffusion layer. Similar to conventional TBC solar cells, the back of the silicon wafer is expected to be designed with a p-region (boron diffusion region) and an n-region (phosphorus diffusion region) distributed in a forked shape. In this step, laser grooving is used to remove the BSG layer on the surface of the pre-designed phosphorus diffusion layer area, and the subsequent alkaline cleaning is used to fully expose the boron diffusion layer in this area, thereby paving the way for subsequent phosphorus diffusion.

[0062] In some specific implementation cases, picosecond laser is used for laser grooving, and the conditions are: laser wavelength 400~600 nm, frequency 500~700 KHz, marking speed 40000~50000 mm / s, power 10~50 W, and processing time 1~5 s.

[0063] S5. Alkaline cleaning to fully expose the boron diffusion layer 3 in the slotted area. The non-slotted area can be protected from alkali corrosion because of the surface protection of the BSG layer 4. Figure 3 shown.

[0064] In some specific implementation cases, the silicon wafer is placed in an alkaline solution for cleaning at a temperature of 75~85°C. During the experiment, by adjusting different parameters such as cleaning time and corresponding ellipsometer testing, the BSG layer in the grooved area can be accurately removed, so that the boron diffusion layer in the grooved area is fully exposed, while at the same time preventing the bottom intrinsic polysilicon layer from being excessively removed during the alkaline cleaning process.

[0065] S6, phosphorus diffusion, so that the exposed boron diffusion layer is converted to a phosphorus atomic concentration of >1E+20 cm -3 Since the boron doping concentration in the boron diffusion layer 3 is relatively low, the present invention diffuses phosphorus atoms into the boron diffusion layer 3 through a suitable phosphorus diffusion process. When the phosphorus atom concentration is higher than the boron atom concentration, the boron diffusion layer 3 can be inverted into a phosphorus diffusion layer 4, and a PSG layer 5 is formed on the surface. The non-laser grooved area can effectively block the entry of phosphorus atoms during the phosphorus diffusion process due to the presence of the surface BSG layer 4, so it can still remain as a boron diffusion layer 3, such as Figure 4 shown.

[0066] In some specific implementation cases, the phosphorus diffusion conditions are: phosphorus diffusion temperature 750-850°C, diffusion time 10-50 min, POCl3 carried by nitrogen with a flow rate of 1000-5000 sccm, O2 flow rate 2000-8000 sccm; oxidation advancement temperature 850-950°C, O2 flow rate 3000-20000 sccm, advancement time 30-90 min. The thickness of PSG formed after phosphorus diffusion is 30-70 nm.

[0067] S7, green laser grooving removes the BSG layer and PSG layer at the junction of the boron diffusion layer and the phosphorus diffusion layer, and loosens the bottom deposition layers (tunneling oxide layer, boron diffusion layer, phosphorus diffusion layer). The green laser grooving area is the pre-designed isolation area (i.e., the insulating Gap area). After removing the BSG layer and PSG layer in this area, an isolation area can be formed after subsequent wet cleaning.

[0068] In some specific implementation cases, the conditions for the green laser grooving are: laser wavelength of 477~592nm, frequency of 500~700KHz, marking speed of 40000~50000 mm / s, power of 40~100 W, and processing time of 1~5 s.

[0069] S8. Use ultraviolet laser grooving to remove the remaining BSG layer on both sides and loosen the surface of the boron diffusion layer at the bottom.

[0070] In some specific implementation cases, the conditions for the ultraviolet laser grooving are: laser wavelength of 200~400nm, frequency of 500~700KHz, marking speed of 40000~50000 mm / s, power of 10~40W, and processing time of 1~3s.

[0071] S9, removing the remaining PSG layer on both sides by ultraviolet laser grooving, and loosening the surface of the phosphorus diffusion layer at the bottom.

[0072] In some specific implementation cases, the conditions for the ultraviolet laser grooving are: laser wavelength of 200~400nm, frequency of 500~700KHz, marking speed of 40000~50000 mm / s, power of 8~30W, and processing time of 1~3s.

[0073] The purpose of S8-S9 UV laser grooving is to remove the two side parts of each remaining BSG layer and the remaining PSG layer, and loosen the surface layer of the boron diffusion layer and the surface layer of the phosphorus diffusion layer at the bottom of the groove area, paving the way for the formation of a convex isolation area structure after subsequent wet cleaning.

[0074] It should be noted that S7 of the present invention uses a green laser, while S8 and S9 use an ultraviolet laser. The present invention cleverly utilizes the fact that the penetration depth of ultraviolet laser is shallower than that of green laser, and on the basis of ensuring the removal of BSG layer and PSG layer, the sedimentary layers at different depths at the bottom can be loosened. During the green laser grooving process, the sedimentary layers (tunneling oxide layer, boron diffusion layer, phosphorus diffusion layer) at the bottom of the grooving area can be loosened, so they can be completely removed during the subsequent wet cleaning process; while the depth of ultraviolet laser grooving is shallow, so only the surface layers of the boron diffusion layer and phosphorus diffusion layer at the bottom of the grooving area can be loosened, so that in the subsequent wet cleaning process, only the surface layers of the boron diffusion layer and phosphorus diffusion layer in the area are accurately controlled to be corroded and removed, thereby forming a convex isolation area structure.

[0075] In addition, in addition to cleverly utilizing the difference in penetration depth of laser wavelength to assist in constructing the convex isolation region structure in S7 and S8 / S9, the present invention also controls the power of the two laser treatments. The present invention further controls the laser power of S7 to be higher and the time to be longer, while the power of the laser treatment of S8 / S9 is relatively low and the time is shorter, so that the processing depth can be further differentiated.

[0076] Furthermore, since the height of the PSG formed during the diffusion of S6 phosphorus is lower than that of the BSG layer (in a "concave" shape), in order to subsequently construct a convex isolation region structure, it is necessary to control the UV laser processing depths of the p-region and the n-region to be different (S8 is deeper). Therefore, the present invention needs to adopt a two-step process to groove the BSG layer and the PSG layer respectively, and control the power of S8 to be slightly higher.

[0077] S10, removing the coating on the front and side surfaces of the silicon wafer.

[0078] In some specific implementation cases, a chain machine (acid etching) is used to remove the boron diffusion layer and phosphorus diffusion layer and other coating layers on the front and side surfaces of the silicon wafer.

[0079] S11, the silicon wafer is wet cleaned and texturized under alkaline conditions. In the area covered by the BSG layer 4 and the PSG layer 6, the bottom boron diffusion layer 3 and the phosphorus diffusion layer 5 are protected from being corroded by alkali. For other areas, due to the different depths of laser loosening in S7 and S8 / S9, the alkali corrosion rate in different areas will be different. The wet etching rate is: V (绿色激光开槽区域) >V (紫外激光开槽区域) Finally, by controlling the cleaning time, the deposition layer of the green laser grooved area on the back of the silicon wafer is removed, and the back of the silicon wafer is exposed. The surface of the boron diffusion layer 3 and the surface of the phosphorus diffusion layer 5 that are loosened in the ultraviolet laser grooved area are removed to form a convex isolation area structure. At the same time, the surface of the isolation area on the front and back of the silicon wafer is textured to form a pyramid texture surface 7; finally, the PSG layer 6 and BSG layer 4 remaining on the back of the silicon wafer are removed by pickling, as shown in FIG. Figure 5 shown.

[0080] In some specific implementation cases, in S11, the width of the surface layer of the boron diffusion layer and the surface layer of the phosphorus diffusion layer that are removed on one side is 25-40% of the entire layer, and the height is 30-80% of the entire layer.

[0081] In some specific implementation cases, the silicon wafer after de-plating is placed in an alkaline texturing tank for wet cleaning and double-sided texturing integrated treatment, wherein the temperature is maintained at 75-85°C for 6-12 minutes.

[0082] S12, double-sided coating: after double-sided coating, a passivation anti-reflection layer 8 is generated on the front and back sides of the silicon wafer.

[0083] S13, screen printing, sintering to form electrode layer 9, light injection, to obtain TBC solar cell, such as Figure 6 shown.

[0084] Specific examples and comparative examples.

[0085] Example 1

[0086] A method for preparing a TBC solar cell by single deposition of a silicon layer without a mask specifically comprises the following steps:

[0087] S1. Double-sided polishing of silicon wafer: Select N-type single crystal silicon wafer 1 cut by diamond wire, with a thickness of 150 μm and a size of 182.2 mm × 186.7 mm. Put the silicon wafer into the alkaline polishing tank, maintain the temperature at 75°C, and perform double-sided polishing for 6 min. The polishing thickness is 4 μm, and the thinning amount is 0.42 g. Figure 1 shown.

[0088] S2. Form a tunnel oxide layer 2 (using LPCVD method) and an intrinsic polysilicon layer 3 (using LPCVD method) on the back side.

[0089] The deposition conditions of the tunneling oxide layer are: O2 flow rate 40000 sccm, reaction temperature 600℃, time 600 s, and the thickness of the tunneling oxide layer is about 3 nm.

[0090] The deposition conditions of the intrinsic polysilicon layer are: SiH4 flow rate 920 sccm, reaction temperature 550℃, time 3.3 h, working gas pressure 300 mTorr, and the thickness of the intrinsic polysilicon layer is about 290 nm.

[0091] S3, boron diffusion, so that the intrinsic polysilicon layer is converted into a boron atomic concentration of 3E+19 cm -3 After boron diffusion, the intrinsic polysilicon layer 2 on the back of the silicon wafer can be converted into a boron diffusion layer 3 and a BSG layer 4, wherein the BSG layer 4 is located on the surface of the boron diffusion layer 3, such as Figure 2 shown.

[0092] The boron diffusion conditions are: temperature 850°C, diffusion time 10 min, BCl3 flow rate 200 sccm, O2 flow rate 1200 sccm; oxidation push temperature 950°C, O2 flow rate 7000 sccm, push time 30 min. The thickness of the BSG layer is about 45 nm.

[0093] S4, use picosecond laser grooving to remove the BSG layer in the designed area of ​​the phosphorus diffusion layer, the conditions are: laser wavelength 532nm, frequency 600KHz, marking speed 45000mm / s, power 50W, processing time 3s. Similar to conventional TBC solar cells, the back of the silicon wafer is expected to be designed with a p-region (boron diffusion region) and an n-region (phosphorus diffusion region) distributed in a forked shape. In this step, laser grooving is used to remove the BSG layer on the surface of the pre-designed phosphorus diffusion layer area, and the subsequent alkaline cleaning is used to fully expose the boron diffusion layer in this area, thereby paving the way for subsequent phosphorus diffusion.

[0094] S5. Alkaline cleaning to fully expose the boron diffusion layer 3 in the slotted area. The non-slotted area can be protected from alkali corrosion because of the surface protection of the BSG layer 4. Figure 3 The specific steps are as follows: put the silicon wafer into an alkaline solution for cleaning at a temperature of 75°C. During the experiment, by adjusting different parameters such as cleaning time and correspondingly matching the ellipsometer test, the BSG layer in the slotted area can be accurately removed, so that the boron diffusion layer in the slotted area is fully exposed, while the bottom intrinsic polysilicon layer is not excessively removed during the alkaline cleaning process.

[0095] S6, phosphorus diffusion, converting the exposed boron diffusion layer to a phosphorus atomic concentration of 2.7E+20 cm -3 Since the boron doping concentration in the boron diffusion layer 3 is relatively low, the present invention diffuses phosphorus atoms into the boron diffusion layer 3 through a suitable phosphorus diffusion process. When the phosphorus atom concentration is higher than the boron atom concentration, the boron diffusion layer 3 can be inverted into a phosphorus diffusion layer 4, and a PSG layer 5 is formed on the surface. The non-laser grooved area can effectively block the entry of phosphorus atoms during the phosphorus diffusion process due to the presence of the surface BSG layer 4, so it can still remain as a boron diffusion layer 3, such as Figure 4 shown.

[0096] The phosphorus diffusion conditions are as follows: phosphorus diffusion temperature 790°C, diffusion time 30 min, POCl3 carried by nitrogen with a flow rate of 3000 sccm, O2 flow rate 5000 sccm; oxidation push temperature 890°C, O2 flow rate 8000 sccm, push time 60 min. The thickness of PSG formed after phosphorus diffusion is about 45 nm.

[0097] S7, green laser grooving removes the BSG layer and PSG layer at the junction of the boron diffusion layer and the phosphorus diffusion layer, and loosens the bottom deposition layers (tunneling oxide layer, boron diffusion layer, phosphorus diffusion layer). The conditions are: laser wavelength of 532 nm, frequency of 600 KHz, marking speed of 45000 mm / s, power of 50 W, and processing time of 3 s. The green laser grooving area is the pre-designed isolation area (i.e., the insulating Gap area). After removing the BSG layer and PSG layer in this area, an isolation area can be formed after subsequent wet cleaning.

[0098] S8, UV laser grooving to remove the remaining BSG layer on both sides and loosen the surface of the boron diffusion layer at the bottom. The conditions of UV laser grooving are: laser wavelength of 355 nm, frequency of 600 KHz, marking speed of 45000 mm / s, power of 20W, and processing time of 1.5 s.

[0099] S9, removing the remaining PSG layer on both sides by ultraviolet laser grooving, and loosening the surface of the phosphorus diffusion layer at the bottom.

[0100] The conditions for UV laser grooving were: laser wavelength of 355 nm, frequency of 600 KHz, marking speed of 45000 mm / s, power of 18 W, and processing time of 1.5 s.

[0101] S10, removing the coating on the front and side surfaces of the silicon wafer: using a chain machine (acid etching) to remove the coatings such as the boron diffusion layer and the phosphorus diffusion layer on the front and side surfaces of the silicon wafer.

[0102] S11. Wet cleaning and texturing of silicon wafers under alkaline conditions: Place the silicon wafers after de-plating in an alkaline texturing tank for wet cleaning and texturing integration, with the temperature maintained at 82°C for 7 minutes. In the areas covered by the BSG layer 4 and the PSG layer 6, the bottom boron diffusion layer 3 and phosphorus diffusion layer 5 are protected from alkali corrosion. For other areas, due to the different depths of laser loosening in S7 and S8 / S9, the alkali corrosion rates in different areas will be different. The wet corrosion rate is: V (绿色激光开槽区域) >V (紫外激光开槽区域) . Finally, by controlling the cleaning time, the deposition layer in the green laser grooved area on the back of the silicon wafer is removed, exposing the back of the silicon wafer, and removing the surface layers of the boron diffusion layer 3 and the phosphorus diffusion layer 5 in the loosened part of the ultraviolet laser grooved area, forming a convex isolation area structure. Among them, the width of the surface layer of the boron diffusion layer and the surface layer of the phosphorus diffusion layer removed on one side is about 30% of the original whole layer, and the height is about 50% of the original whole layer. At the same time, the surface of the isolation area on the front and back of the silicon wafer is textured to form a pyramid velvet surface 7; finally, the residual PSG layer 6 and BSG layer 4 on the back of the silicon wafer are removed by pickling, as shown in FIG. Figure 5 shown.

[0103] S12, double-sided coating: after double-sided coating, a passivation anti-reflection layer 8 is formed on the front and back sides of the silicon wafer. Specifically, it includes: using ALD deposition method to deposit AlO on the front and back sides of the processed silicon wafer. x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of 8nm and a process temperature of 250°C. Then, SiN is deposited on both sides using a tubular PECVD device. x Film, front SiN x The thickness of the film is about 82 nm, and the refractive index is 2.1; the back SiN x The thickness of the film is about 90 nm and the refractive index is 2.0; the reaction gases in the tubular cavity are SiH4 and NH3, the working pressure is 1600 mTorr, the power is 12000 W, the temperature is 440℃, the SiH4 gas flow rate is 980 sccm, the NH3 gas flow rate is 8000 sccm, the silicon-nitrogen ratio is 1:5, and the deposition time is 10 min.

[0104] S13, screen printing the coated silicon wafer on the back to form a metal contact, then sintering at 770°C to form an Ag-Si ohmic contact (electrode layer 9), and finally performing light injection repair to obtain a TBC solar cell, such as Figure 6 shown.

[0105] Comparative Example 1 (using two depositions of intrinsic polysilicon layer)

[0106] S1. Select N-type single crystal silicon wafers cut with diamond wire, with a thickness of 150 μm and a size of 182.2 mm×186.7 mm. Put the cut silicon wafers into an alkaline polishing tank, maintain the temperature at 75°C, and perform double-sided polishing for 6 min. The polishing thickness is 4 μm and the thinning amount is 0.42 g.

[0107] S2. Subsequently, a tunneling oxide layer is first grown on the back surface of the polished silicon wafer using LPCVD, with an O2 gas flow rate of 40,000 sccm, a temperature of 600°C, and a growth time of 600 s. The thickness of the grown tunneling oxide layer is about 3 nm. Then, an intrinsic polysilicon layer is grown again on the basis of the tunneling oxide layer, with an SiH4 gas flow rate of 920 sccm, a temperature of 550°C, a growth time of 3.3 h, a working pressure of 300 mTorr, and a thickness of the intrinsic polysilicon layer of about 290 nm.

[0108] S3. Then, a high-temperature boron diffusion method is used to transform the inner layer and the surface layer of the intrinsic polysilicon layer into a boron diffusion layer and a BSG layer, respectively. The boron diffusion temperature is 850°C, the diffusion time is 10 min, the BCl3 gas flow rate is 200 sccm, the O2 gas flow rate is 1200 sccm, the oxidation advancement temperature is 950°C, the O2 flow rate is 7000 sccm, the advancement time is 30 min, and the BSG layer thickness is about 45 nm.

[0109] S4. Use picosecond laser to perform a patterned grooving of the BSG layer. The laser wavelength used is 532 nm, the frequency is 600 KHZ, the marking speed is 45000 mm / s, the power is 50 W, and the processing time is 3 s.

[0110] S5. The silicon wafer after laser patterning and slotting is placed in an alkaline solution for cleaning at a temperature of 75°C for 360 s and a corrosion depth of 1.7 μm.

[0111] S6. Then, a tunneling oxide layer is grown for the second time on the back surface of the silicon wafer by LPCVD. The gas flow rate of O2 is 30,000 sccm, the temperature is 600°C, the time is 450 s, and the thickness of the grown tunneling oxide layer is about 2.5 nm. Then, an intrinsic polysilicon layer is grown again on the basis of the tunneling oxide layer. The gas flow rate of SiH4 is 920 sccm, the temperature is 550°C, the time is 1.5 h, the working pressure is 300 mTorr, and the thickness of the intrinsic polysilicon layer is about 180 nm.

[0112] S7. The inner layer and the surface layer of the intrinsic polysilicon layer are transformed into a phosphorus diffusion layer and a PSG layer respectively by the phosphorus diffusion method. The phosphorus diffusion temperature is 790°C, the diffusion time is 15 min, POCl3 is carried by nitrogen with a flow rate of 1000 sccm, the O2 flow rate is 650 sccm, the oxidation advancement temperature is 890°C, the O2 flow rate is 3000 sccm, the advancement time is 20 min, and the PSG layer thickness is about 39nm.

[0113] S8. Then, a picosecond laser is used to perform secondary patterning and grooving of the PSG layer to loosen the PSG layer corresponding to the bottom of the boron diffusion layer and the PSG layer at the junction of the p-region and the n-region. The laser wavelength is 532 nm, the frequency is 600 KHz, the marking speed is 45000 mm / s, the power is 25 W, and the processing time is 2.7 s.

[0114] S9. Use a chain machine to remove the boron diffusion layer and phosphorus diffusion layer plated on the front and side surfaces of the silicon wafer.

[0115] S10, put the silicon wafer that has been deplated into the alkaline texturing tank for wet cleaning and texturing of the laser slotted area on the back side, maintain the temperature at 82°C for 7 minutes, lose 0.36 g, and perform cleaning and texturing. Since the silicon wafer has been deplated and there is no oxidation area on the front side, an effective light-trapping velvet surface can be formed during the texturing process; and in the laser patterning area on the back side, the alkaline solution can effectively corrode the bottom deposition layer to form an isolated insulating structure. The subsequent acid cleaning tank of the texturing tank can further remove the PSG layer and BSG layer remaining on the silicon wafer.

[0116] S11, using ALD deposition method to deposit AlO on the front and back sides of the processed silicon wafer x The film is generated by the reaction of Al(CH3)3 and water vapor, with a thickness of 8 nm and a process temperature of 250°C. Then, SiN is deposited on both sides using a tubular PECVD device. x Film, front SiN x The thickness of the film is about 82 nm, and the refractive index is 2.1; the back SiN x The thickness of the film is about 90 nm and the refractive index is 2.0; the reaction gases in the tubular cavity are SiH4 and NH3, the working pressure is 1600 mTorr, the power is 12000 W, the temperature is 440℃, the SiH4 gas flow rate is 980 sccm, the NH3 gas flow rate is 8000 sccm, the silicon-nitrogen ratio is 1:5, and the deposition time is 10 min.

[0117] S12. The coated sheet is screen-printed on the back to form a metal contact, and then sintered at 770°C to form an Ag-Si ohmic contact. Finally, the final TBC finished battery is obtained through light injection repair.

[0118] Comparative Example 2

[0119] The difference between Comparative Example 2 and Example 1 is that S8-S9 is not included, that is, S10 is directly performed after S7 of Example 1, and the isolation region of the TBC solar cell finally obtained does not have a convex isolation region structure, but is in a conventional rectangular shape.

[0120] Performance comparison

[0121] Table 1: Electrical performance data of different solar cells

[0122]

[0123] From the data in the above table, we can see that:

[0124] First, since Example 1 adopts a one-step process of depositing an intrinsic polysilicon layer, while Comparative Example 1 adopts a conventional process of depositing an intrinsic polysilicon layer twice in succession, the TBC solar cell obtained in Example 1 has better performances, especially a higher short-circuit current density ( J sc ), poly-Si parasitic absorption is lower.

[0125] Secondly, the TBC solar cell finally obtained in Example 1 has a convex isolation region structure, and its battery performance is better than that of Comparative Example 2, especially the poly-Si parasitic absorption is further reduced, and the battery leakage value ( Irev ) is also further improved compared with Comparative Example 2.

[0126] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.

[0127] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a TBC solar cell by single deposition of a silicon layer without a mask, characterized in that include: S1, double-sided polishing of silicon wafer; S2, forming a tunnel oxide layer and an intrinsic polysilicon layer on the back side; S3, boron diffusion, so that the intrinsic polysilicon layer is converted into a boron atomic concentration of 1E+19~1E+20 cm -3 Boron diffusion layer and BSG layer; S4, laser grooving to remove the BSG layer in the designed area of ​​the phosphorus diffusion layer; S5, alkali cleaning; S6, phosphorus diffusion, so that the exposed boron diffusion layer is converted to a phosphorus atomic concentration of >1E+20 cm -3 Phosphorus diffusion layer and PSG layer; S7, removing the BSG layer and the PSG layer at the junction of the boron diffusion layer and the phosphorus diffusion layer by green laser grooving, and loosening the deposited layers at the bottom thereof; the deposited layers are the tunneling oxide layer, the boron diffusion layer and the phosphorus diffusion layer; S8, removing the two side portions of the remaining BSG layer by ultraviolet laser grooving, and loosening the surface layer of the boron diffusion layer at the bottom thereof; S9, removing the two side portions of the remaining PSG layer by ultraviolet laser grooving, and loosening the surface layer of the phosphorus diffusion layer at the bottom; S10, removing the coating; S11, the silicon wafer is wet cleaned and textured simultaneously under alkaline conditions, the deposition layer loosened by S7 and the surface layers of the boron diffusion layer and the phosphorus diffusion layer loosened by S8 and S9 are removed to form a convex isolation area structure; at the same time, a pyramid texture surface is formed in the exposed area on the surface of the silicon wafer; finally, the residual PSG layer and BSG layer are removed by pickling; S12, double-sided coating; S13, screen printing, sintering, light injection.

2. The method according to claim 1, characterized in that: In S3, the boron diffusion conditions are: boron diffusion temperature 800~950℃, diffusion time 5~50 min, BCl3 flow rate 50~500 sccm, O2 flow rate 500~2000 sccm; oxidation advancement temperature 900~1050℃, advancement time 30~80 min, O2 flow rate 5000~30000 sccm.

3. The method according to claim 2, characterized in that: In S3, the thickness of BSG formed after boron diffusion is 30 to 70 nm.

4. The method according to claim 1 or 2, characterized in that: In S6, the phosphorus diffusion conditions are: phosphorus diffusion temperature 750~850℃, diffusion time 10~50 min, POCl3 is carried by nitrogen with a flow rate of 1000~5000 sccm, and O2 flow rate 2000~8000 sccm; oxidation advancement temperature 850~950℃, O2 flow rate 3000~20000 sccm, and advancement time 30~90min.

5. The method according to claim 4, characterized in that: In S6, the thickness of PSG formed after phosphorus diffusion is 30 to 70 nm.

6. The preparation method according to claim 1, characterized in that: In S7, the conditions for the green laser grooving are: laser wavelength of 477-592 nm, power of 40-100 W, and processing time of 1-5 s; In S8, the conditions of the ultraviolet laser grooving are: laser wavelength is 200-400 nm, power is 10-40 W, and processing time is 1-3 s; In S9, the conditions for the ultraviolet laser grooving are: laser wavelength is 200-400 nm, power is 8-30 W, and processing time is 1-3 s.

7. The method according to claim 1 or 6, characterized in that: In S11, the width of the surface layer of the boron diffusion layer removed on one side is 25-40% of the entire boron diffusion layer, and the height is 30-80% of the entire boron diffusion layer; the width of the surface layer of the phosphorus diffusion layer removed on one side is 25-40% of the entire phosphorus diffusion layer, and the height is 30-80% of the entire phosphorus diffusion layer.

8. The method according to claim 1, characterized in that: In S2, the deposition conditions of the tunnel oxide layer are: O2 flow rate 10000~80000 sccm, reaction temperature 400~800°C, time 200~1000 s, and tunnel oxide layer thickness 2~10 nm.

9. The method according to claim 1, characterized in that: In S2, the deposition conditions of the intrinsic polysilicon layer are: SiH4 flow rate 300~2000 sccm, reaction temperature 500~700°C, time 2~4 h, working gas pressure 100~500 mTorr, and intrinsic polysilicon layer thickness 100~300 nm.